Effect of Sesamum indicum leaves on growth performance and carcass characteristics of broiler chicken - Adedeji, O.S.; Amao, S.R.; Olugbemiga, K.S. (Nigerian Journal of Animal Science, 2023)
The study was conducted to determine the effect of Sesamum indicum leaves on growth performances, carcass characteristics, primal cuts and organs’ weights of broiler chicken fed from day old to eight weeks. A total of 150 broiler chicks were partitioned into 5 treatments, where each treatment had 3 replicates with 10 birds per replicate and grinded-air dried leaves of Sesamum indicum leaves were administered into their feed. Treatment I (T1) served as control containing 0 % of Sesamum indicum leaves, treatments II (T2), III (T3), IV (T4) and V (T5) were given 10 g, 20 g, 30 g and 40 g per kg of feed, respectively. As animals were housed under identical condition of temperature and humidity while feed and water was made available ad-libitum. Also, necessary vaccinations and medications were administered to the group I birds. The experiment lasted 8 weeks. At the end of 4 and 8 weeks respectively, data were obtained for total feed intake, weight gain, feed conversion ratio of the birds and also, carcass evaluation were carried out on random sample of birds from each replicate. Results indicated that growth performances, carcass characteristics, primal cuts and organs’ weights were significantly (P< 0.05) affected most of the parameters measured. The inclusion of Sesamum indicum leaves into broiler diet at 10g/kg treatment had almost the similar body weight, improvement in weekly gain in weight and feed efficiency and carcass assessment as compared to that of control group of broilers.